Virtual Reality in Gaming (International Journal of Innovative Research in Computer Science & Technology, 2022)
Augmented reality (VR) gaming is  another sort of PC game which utilizes computer generated  reality (VR) innovations that can give clients a totally  practical, first-individual viewpoint of the game activity.  Designing multiplayer virtual reality games is difficult  because real-world influences can easily detract from  immersion. In the 20th century, video games became the  most important forms of entertainment. Its influence has  multiplied and vastly enhanced in the twenty-first century.  The gaming business was changed in such new market  platforms with the introduction of mobile phones as well  as portable devices. However, in order to establish virtual  reality gaming as a credible new medium, it is necessary to  provide enjoyable and social virtual reality experiences. This paper discuss design strategies for incorporating  social interactions throughout game design while retaining  immersion. The authors discuss the game design of such a  collaborative regional multi-player/platforms virtual  reality game as well as the effect of virtual reality on  playing both from an enterprise as well as a player's  perspective in this article to illustrate how our  methodologies may be used and how successful they are.  Virtual reality technologies are fast gaining popularity  across a wide range of sectors. Virtual reality is changing  the way things are done in a range of sectors, from health  to automotive, because there are great expectations for the  future, particularly in the case of video games.
Keywords: Immersion; Multiplayer; Social Interaction; Virtual Reality; Video Gaming; Virtual Reality Gaming